Simulating the Ring Current Proton Dynamics in Response to Radial Diffusion by Ultra‐Low‐Frequency (ULF) Waves - Longxing Ma; Yiqun Yu; Wenlong Liu; Jinbin Cao; Yoshizumi Miyoshi (Geophysical Research Letters)
Abstract Radial diffusion (RD) induced by ULF waves can contribute to particle acceleration and scattering. Past global simulations that incorporate RD often use dipole magnetic fields, which could not realistically reveal the role of RD. To better understand the effects of RD and identify whether a background magnetic field model matters in understanding the ring current dynamics in response to RD, we simulate a storm event with different magnetic configurations using a global kinetic ring current model. Results indicate that RD can effectively diffuse protons of hundreds of keV to inner regions (L ∼ 3.5), especially in recovery phase. Comparisons with in‐situ observations demonstrate that simulations with TS05 overall capture both the intensity and variations of proton fluxes with the aid of RD, whereas that with a dipole field significantly overestimates low‐L region fluxes. This study implies adopting realistic magnetic fields is important for correctly interpreting the role of RD.